In Vitro Study of the influence of the pigments of three colored gels over the light distribution of visible light by digital images - Florez, F. L. E. [UNESP]; Figueiredo, A. C. R.; Moriyama, L. T.; Oliveira Junior, O. B. [UNESP]; Bagnato, V. S. (Spie - Int Soc Optical Engineering, 2009)
Nowadays the real contribution of light on the acceleration of the chemical reaction for the dental bleaching is under incredulity, mostly because the real mechanisms of its contribution still are obscure. Objectives: Determine the influence of pigment of three colored bleaching gels in the light distribution and absorption in the teeth, to accomplish that, we have used in this experiment bovine teeth and three colored bleaching gels. It is well Known that the dark molecules absorb light and increase the local temperature upraising the bleaching rate, these molecules are located in the interface between the enamel and dentin. Methods: This study was realized using an argon laser with 455nm with 150mW of intensity and a LED with the same characteristics, three colored gels (green, blue and red) and to realize the capture of the digital images it was used a CCD camera connected to a PC. The images were processed in a mathematical environment (MATHLAB, R12 (R)). Results: The obtained results show that the color of the bleaching gel influences significantly the absorption of light in the specific sites of the teeth. Conclusions: This poor absorption can be one of the major factors involved with the incredulity of the light contribution on the process that can be observed in the literature nowadays.